2016
DOI: 10.1186/s40064-016-3383-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of absorbed irrigation fluid volumes during retrograde intrarenal surgery and percutaneous nephrolithotomy for the treatment of kidney stones larger than 2 cm

Abstract: PurposeIrrigation-induced increase in intrarenal pressure is of concern because it may cause infection due to increased pyelovenous and pyelolymphatic absorption. This study is the first to compare prospectively the absorbed fluid volumes during percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) for stones larger than 2 cm.Materials and methodsGeneral anesthesia was applied to all patients. Isotonic solution containing 1 % ethanol was used as irrigation fluid. Venous blood ethanol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 26 publications
1
18
1
2
Order By: Relevance
“…[5] and recently by Guzelburc et al . [11] However, our study also shows that the height of irrigating fluid and total time for irrigation do not show any correlation with the above-mentioned indices. Height of irrigating fluid is an important determinant of fluid absorption during the TURP.…”
Section: Discussioncontrasting
confidence: 61%
“…[5] and recently by Guzelburc et al . [11] However, our study also shows that the height of irrigating fluid and total time for irrigation do not show any correlation with the above-mentioned indices. Height of irrigating fluid is an important determinant of fluid absorption during the TURP.…”
Section: Discussioncontrasting
confidence: 61%
“…The most frequent complication in laser lithotripsy is fever [ 102 ]. Renal backflow and infected urine fluid reabsorption can be one of the causes, and curiously retrograde intrarenal surgery (RIRS) has higher total fluid absorption than percutaneous nephrolithotomy (PCNL) procedures [ 103 ], which makes sense considering the enclosed space in RIRS. The presence of a preoperative stent, obstructive pyelonephritis, a positive preoperative bladder urine culture result, female gender, increased stone size, or lengthy operating time are significantly associated with postoperative fever and risk of sepsis [ 104 , 105 ].…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…They performed a volumetric fluid balance and concluded that routine URS is associated with minimal systemic fluid absorption and sterile water for URS is safe even if ureteral perforation occurs. Conversely, in a prospective study which ethanol 1% was used as irrigant, it has been showed that absorbed fluid during RIRS was not negligible [ 17 ]. Zeltser et al stated in their commentary that even though sterile water has better visuality, isotonic saline should be the irrigant of choice in ureterorenoscopic procedures since sterile water may cause serious complications including cardiovascular collapse, in accordance to their personal observations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%